2004
DOI: 10.1289/ehp.6804
|View full text |Cite
|
Sign up to set email alerts
|

Medications as a source of human exposure to phthalates.

Abstract: Phthalates are a group of multifunctional chemicals used in consumer and personal care products, plastics, and medical devices. Laboratory studies show that some phthalates are reproductive and developmental toxicants. Recently, human studies have shown measurable levels of several phthalates in most of the U.S. general population. Despite their widespread use and the consistent toxicologic data on phthalates, information is limited on sources and pathways of human exposure to phthalates. One potential source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
3
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(162 citation statements)
references
References 28 publications
(27 reference statements)
4
148
3
7
Order By: Relevance
“…Furthermore, we want to point out that both models are not based on worst case assumptions but try to accommodate the most likely exposure scenario for each individual child. As two case studies in the US and Germany have shown (Hauser et al, 2004;Koch et al, 2005a), actual individual exposures to DnBP through medications can be manifold higher than reported in this study.…”
Section: Resultscontrasting
confidence: 43%
See 2 more Smart Citations
“…Furthermore, we want to point out that both models are not based on worst case assumptions but try to accommodate the most likely exposure scenario for each individual child. As two case studies in the US and Germany have shown (Hauser et al, 2004;Koch et al, 2005a), actual individual exposures to DnBP through medications can be manifold higher than reported in this study.…”
Section: Resultscontrasting
confidence: 43%
“…In two case studies both in the USA and in Germany, extraordinary high urinary MnBP concentrations (16.9 mg/l and 31.0 mg/l) were reported after DnBP-containing medications have been taken (Hauser et al, 2004;Koch et al, 2005a). These values are about a 100-1000 times higher than the median values in all previously investigated populations.…”
Section: Metabolites In Urinementioning
confidence: 99%
See 1 more Smart Citation
“…Phthalates also are used as industrial solvents and lubricants, additives in the textile industry, in pesticide formulations and as components in personal-care products (David et al 2001;EC 2008). One of them, dibutyl phthalate (DBP), is also used in the pharmaceutical field as a constituent of the enteric coating of some medications (Hauser et al 2004).…”
Section: Phthalates and Bisphenol A (A) Their Use In Plastic Manufacturementioning
confidence: 99%
“…PEs are used extensively as plasticizers, in several consumer plastic products, including children toys, food wrappings, cosmetics, paints, some biomedical devices (e.g. dialysis tubing and intravenous bags), and enteric coatings of some pharmaceuticals (Hauser et al, 2004;Oehlmann et al, 2009). Because PEs are not covalently bound to polymer plastics, they can easily leach out over time into the environment, reaching humans and wildlife species through ingestion, inhalation, and dermal exposure (Heudorf et al, 2007).…”
Section: Introductionmentioning
confidence: 99%